Gastric lavage and enteral feeding problems in late preterm and term neonates born with meconium stained amniotic fluid - Prashant Bhadane (Sociedad Ecuatoriana de Pediatría (Núcleo de Quito), 2023)
Introduction: Prenatal issues such as pregnancy-induced hypertension, antepartum toxemia, obstructed or delayed labor, and fetal discomfort are standard in MSAF-positive pregnancies. In the early neonatal period, a proportion of infants born through meconium-stained amniotic fluid may swallow meconium and have nausea, vomiting, retching, various feeding issues such as poor sucking, and subsequent aspiration after vomiting. We conducted this observational study to see if stomach wash decreases the requirement for subsequent stomach wash in neonates born via MSAF soon after delivery, as indicated by feed intolerance. Methods: An observational study was performed on newborns diagnosed with meconium-stained liquor for a duration of 6 months. Results: From 1103 neonates, 110 (9.9%) were born with MSAF during the study period. Eight (8%) infants required additional stomach washing within the first 48 hours of life. 18 infants (18.0 %) experienced at least one episode of vomiting. Only 8 of them needed further gastric lavage to resume eating. Five out of one hundred infants (5/100) had regurgitation (more than one episode). No newborns required parental fluids in the first 48 hours. Baseline parameters like gestational age, birth weight, gender, mode of delivery, Apgar score at 1 and 5 minutes, and meconium consistency were observed. Conclusions: Gastric lavage has been frequently performed as part of crucial newborn care for infants with meconium-tainted amniotic fluid. According to the findings of this study, gastric lavage should be reserved for treating the relatively uncommon occurrence of feed intolerance in neonates born with MSL rather than being used as a routine prophylactic measure.